SLOW SLIP EVENTS: PARAMETERS, CONDITIONS OF OCCURRENCE, AND FUTURE RESEARCH PROSPECTS - G. G. Kocharyan; S. B. Kishkina; V. A. Novikov; A. A. Ostapchuk (Геодинамика и тектонофизика)
Slow slip events along faults and fractures are reviewed. Such inter-block displacements can be recorded at various scale levels and considered as transitional from quasi-stable (creep) to dynamic slip (earthquake). Such events include seismogenic slip along faults at velocities by one to three orders lower than those in case of 'normal' earthquakes, as well as aseismic slip cases. Discovering such events facilitates better understanding of how energy accumulated during deformation of the crust is released.Studying conditions and the evolution of transitional regimes can provide new important information on the structure and regularities of deformation in fault zones.Data from latest publications by different authors are consolidated, and the data analysis results are presented. Over 170 slow slip events are reviewed. Based on the consolidated data and modelling results obtained by the authors, relationships between parameters of the reviewed process are established, scale relations between the events are considered, and a first-approximation analysis is conducted for impacts of geomaterial characteristics on various deformation regimes.Low-frequency earthquake foci and slow slip sites are most typically located in zones of transition from stable creep areas to seismogenic segments of the discontinuity (Fig. 3) It can be logically supposed that in such transitional zones, the interface has specific frictional properties providing for a regime that can be termed as 'conditionally stable slip'.The duration of slow deformation events is roughly proportional to the released seismic moment, while such a ratio is close to self-similarity in case of 'normal' earthquakes (Fig. 4). In case of slow slip, an area of the displaced section is larger by many factors than the corresponding value for an earthquake with the same seismic moment, while an average displacement amplitude along the fault is significantly smaller (Figures 5 and 6). Velocities of slip propagation along the fault strike are variable from a few hundred metres to 20–30 km/day. Slip velocities tend to decrease with scale (Fig. 7).Various slip modes were realized in laboratory experiments with slider model. Main specific features of slow slip along faults were simulated in the laboratory conditions. Possibilities for implementation of different deformation regimes were mainly determined by structure of simulated fault gouge. At equal Coulombic strength, small variations of structural characteristics, such as granulometric composition, grain shape, presence of fluid and its viscosity, may critically impact the deformation mode (Fig. 12).As evidenced by the data consolidated and analysed in this article, conditionally stable regimes of deformation of crustal discontinuities are a common phenomenon. Studies of such transitional deformation regimes seem promising for establishment of regularities in generation and evolution of dynamic events, such earthquakes, tectonic rock bursts, and slope events.